PENINGKATAN UMKM MELALUI SOSIALISASI LAPORAN KEUANGAN SEDERHANA DI KELURAHAN DAMAI BARU KECAMATAN BALIKPAPAN SELATAN - Abdiannur Abdiannur; sudjinan sudjinan (Fakultas Ekonomi Universitas Balikpapan, 2019)
This community service activity is entitled Improvement of UMKM through the dissemination of simple financial reports in Damai Baru Sub-District, South Balikpapan District. The purpose of this service is to socialize the importance of simple financial reports for small and micro medium entrepreneurs. From the results of socialization and mentoring in making simple financial reports can facilitate UMKM actors in distinguishing between capital and profits, can know the extent to which the business development and can classify capital and income to know where and where the money is spinning. In addition, business people also understand more about investment and how to compete in a healthy manner with fellow business people in the Damai Baru sub-district, South Balikpapan District.